Metaphysical commentaries by Jean Buridan - the state of research - Mansfeld, Monika (Folia Philosophica, 2012)
The paper presents remaining manuscripts of Quaestiones in duodecim libros „Metaphysicorum” Aristotelis by Jean Buridan and the way in which they were divided into different redactions. Although Buridan’s commentaries were enormously popular at all European universities of late the Middle Ages and early Renaissance, they have not yet been adequately studied. Both their chronology and relations between different manuscripts in which the commentary was handed down remain unclear. Nine manuscripts containing Buridan’s commentary to Metaphysics are known. The most important research on them were done by B. Michael and L.M. de Rijk. Their results show that there are probably three different redactions of this text. Redaction A seems to be the oldest one and it is dated from the earliest years of Buridan’s lectures at University of Paris (1340s). Redaction B is surely the newest one. There is also the third redaction, “the lecture from Erfurt” (lectura Erfordiensis), yet, its relation with other manuscripts has not been defined so far. In my paper I focus on presenting the most important doctrinal, methodological and stylistic differences which make singling out of three redactions possible.